2023
DOI: 10.1158/1078-0432.ccr-23-0422
|View full text |Cite
|
Sign up to set email alerts
|

Cancer's Dark Matter: Lighting the Abyss Unveils Universe of New Therapies

Abstract: The authors of a recent study identified non-canonical peptides (NCP) presented by cancer cells’ HLA and observed lack of reactivity to these antigens by endogenous tumor-reactive T cells. In vitro sensitization generated NCP-reactive T cells that recognized epitopes shared by a majority of cancers tested, providing opportunities for novel therapies to shared antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Another group has explored the immunogenicity of non-canonical HLA-I tumor antigens identified through proteogenomics and shown that at least some of them are immunogenic (IFNg production and upregulation of 4-1BB) and shared across patients [ 82 ]. Their and our data reinforce the potential of TSAs as targets for off-the-shelf vaccines or TCR-based immunotherapies [ 83 ]. Furthermore, a multi-target approach in immunotherapy can enhance treatment effectiveness, improve patient outcomes, and decrease the likelihood of cancer recurrence [ 84 ], positioning immunogenic TSAs as appealing targets for designing multi-epitope vaccines.…”
Section: Discussionsupporting
confidence: 83%
“…Another group has explored the immunogenicity of non-canonical HLA-I tumor antigens identified through proteogenomics and shown that at least some of them are immunogenic (IFNg production and upregulation of 4-1BB) and shared across patients [ 82 ]. Their and our data reinforce the potential of TSAs as targets for off-the-shelf vaccines or TCR-based immunotherapies [ 83 ]. Furthermore, a multi-target approach in immunotherapy can enhance treatment effectiveness, improve patient outcomes, and decrease the likelihood of cancer recurrence [ 84 ], positioning immunogenic TSAs as appealing targets for designing multi-epitope vaccines.…”
Section: Discussionsupporting
confidence: 83%
“…The combination of PD-1 inhibitor, multivalent DRibbles vaccine and GITR agonist has shown increased efficacy in preclinical models [63] and is being tested in a clinical trial of DRibbles vaccine ± GITR agonist, followed after two weeks by delayed anti-PD-1. DPV-001 (DRibbles vaccine) is an off-the-shelf multivalent autophagosomeenriched cancer vaccine that contains > 300 putative cancer antigens, including alternative cancer neoantigens-cancer's dark matter, DAMPS, HSPs and agonists for TLR 2, 4, 7, 8, and NOD2 [64]. INCAGN01876 (GITR agonist) is a recombinant, humanized IgG1 κ monoclonal antibody that selectively binds to the extracellular domain of human GITR (CD357 or TNRSF18).…”
Section: Preliminary Immunological Monitoring Of First-in-human Immun...mentioning
confidence: 99%
“…In addition, among the nascent proteins, misfolded proteins and the population called short‐lived proteins (SLiPs) and defective ribosomal products (DRiPs) are also known to become antigen sources for HLA class I immunopeptides. 16 To trim these source proteins/peptides into a more desirable property as immunopeptides to make the HLA complex, proteasomal degradation and endopeptidase activity are required. More recently, the ubiquitin proteasome system (UPS)‐independent source supply has been also reported.…”
Section: Introductionmentioning
confidence: 99%